Adaptation to drought/delayed rainfall in rice cultivation, Bihar, India. - Munshi, Sugandha; Samaddar, Arindam; Srivastava, Amit; Urfels, Anton; Patil, Vikram; Sherpa, Sonam; Bhanjdeo, Arunditha; Veettil, Prakashan Chellattan; Malik, R. K.; Craufurd, Peter Q.; Kumar, Virender (CGIAR Initiative on Excellence in Agronomy, 2024)
This report presents findings from 21 Focus Group Discussions (FGDs) conducted in seven districts of Bihar namely Muzaffarpur, Madhubani, Samastipur, Vaishali, Gaya, Nalanda, and Lakhisarai with 221 farmers 116 female and 105 males to establish a deeper understanding of the challenges and coping mechanisms in the rice-wheat system related to climate change variabilities faced by farmers in the region. The findings also highlight the opportunities and suggestive interventions for strengthening farmers capacities to deal with the challenges. The study was conducted as part of the Excellence in Agronomy (EiA) initiative use case on “Managing time in the rice-based cropping systems of South Asia”. FGDs were conducted with three groups of farmers in each of the seven districts: Demonstration or Demo farmers, non- Demo farmers and JEEViKA farmers to capture their varied perspectives on challenges and opportunities in rice-wheat cropping systems. The findings present that the rice wheat cropping system is the dominant cropping systems across the districts where Rice in Kharif and Wheat in Rabi are the predominant crop. As far as the engagement of household members in agriculture is concerned, it was found that both men and women are involved in agriculture but with variations related to the degree of women’s active involvement based on farmer categories. For example, in the big farmers household no female members were involved in the agriculture operations on the field and on the other hand the involvement of female members of small and marginal farmers are quite common. In general children’s engagement in agriculture was found very limited and that too mainly carrying meals to the farm.